Exploring the Potential of Jackfruit (Artocarpus heterophyllus Lam) - Nansereko, Sophie; Muyonga, John H. (Asian Food Science Journal, 2021)
Jackfruit (Artocarpus heterophyllus Lam) is widely cultivated in tropical and subtropical areas worldwide. The tree is highly productive, resilient, and requires minimal care. Jackfruit has a characteristic flavour and is highly versatile. Several studies report the importance of the tree and fruits, ranging from food and medicine to the provision of several value-added products. In spite of the many benefits the plant offers, it has not been sufficiently incorporated in the general food system, partly because of gaps in processing, distribution and knowledge about utilization methods and nutritional and nutraceutical value. Objective: A comprehensive literature search was done to highlight jackfruit's nutritional, health, and commercial benefits to promote its utilization. Methodology: The literature search was conducted using three electronic databases with no constraints on publication year. Over 200 studies on the nutritional properties of jackfruit and at least 105 articles on the use of the various parts of the jack tree for their anticarcinogenic, antimicrobial, antifungal, anti-inflammatory, and hypoglycemic effects were found. Findings: Jackfruit has vital nutrients, including phytochemicals, minerals, vitamins, carbohydrates, and proteins. The literature on utilization shows that the fruit can be processed into commercial products using minimal processing technologies, dried to extend product shelf-life, or processed into various value-added products.
Keywords: Jackfruit; nutritional benefits; processing; value addition